2015 IEEE International Conference on Robotics and Biomimetics (ROBIO) 2015
DOI: 10.1109/robio.2015.7418785
|View full text |Cite
|
Sign up to set email alerts
|

A bilateral rehabilitation method for arm coordination and manipulation function with gesture and haptic interfaces

Abstract: Disabilities after neural injury such as stroke bring tremendous burden to the patients, families and society. Besides the conventional constrained-induced training with the paretic arm, bilateral rehabilitation training involves both the ipsilateral and contralateral sides of the neural injury, fits well the fact that both arms are needed in common activities of daily living (ADLs), and can promote good functional recovery. In this work, a bilateral rehabilitation training method is proposed and implemented w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The repeatability error is less than 0.17 mm. Thus, the Leap Motion device offers a portable, compact economic and reasonably precise sensor solution to realize various human-machine interaction applications in the field of AAL (ambient assisted living) and ADLs [ 30 , 31 , 32 ], especially for the elderly and disabled users.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The repeatability error is less than 0.17 mm. Thus, the Leap Motion device offers a portable, compact economic and reasonably precise sensor solution to realize various human-machine interaction applications in the field of AAL (ambient assisted living) and ADLs [ 30 , 31 , 32 ], especially for the elderly and disabled users.…”
Section: Methodsmentioning
confidence: 99%
“…The 4 DOFs’ precise force feedback is provided during the active translational and grasping movements [ 30 ]. The movement range for grasping is 25 mm, with a resolution of 0.006 mm, and the force feedback is up to ±8.0 N, enabling dexterous manipulation and haptic interaction [ 4 , 31 ]. The workspace for translational movements is Φ160 × 110 mm 3 , with a resolution of better than 0.01 mm, and the force feedback can go up to 12.0 N. The rotational workspace of the omega.7 device is 240 × 140 × 180 in degrees, with a resolution of 0.09 degrees.…”
Section: Methodsmentioning
confidence: 99%
“…The movement of distal arm for each subject was recorded during wrist FE motion through the Leap Motion sensor. The Leap Motion sensor offers novel solutions to track the motion of human hands and fingers and record discrete positions and gestures of distal arm within intimate proximity of operating space [23], [24], [25]. Study addressing the tracking accuracy and robustness of the optical device has reported that an overall average accuracy of 0.7 mm was achieved among static and dynamic measurement.…”
Section: E Participants and Experimental Proceduresmentioning
confidence: 99%